PARTISIPASI PETANI DALAM PROGRAM KLASTER PERTANIAN MODERN DI KECAMATAN TAWANGSARI, KABUPATEN SUKOHARJO - Atika Adiarsi; Sapja Anantanyu; Arip Wijianto (AGRITEXTS: Journal of Agricultural Extension, 2020)
Farmers’participation is importantly studied to improve farmers’involvement of agricultural program. Objectives of this research were 1) to study about level of farmers’ participation of modern agricultural cluster program, 2) to study about factors which affected farmers’ participation, 3) to study about correlation between factors which affected the participation and level of farmers’participation. This research used quantitative method with technique of survey. The location that was chosen in Tawangsari district. The population of this research was farmers which were incorporated a combined farmers’ group, Tani Mandiri. This research used technique of proportional random sampling and the respondents were taken sixty farmers from each farmers’ group. The data on this research was shown with likert scale and testing the correlation used analysis of rank spearman. The result showed 1) farmers’ participation was included in high category. Planning, monitoring and evaluation and utilization of the result that included in high category, whereas for the implementation included in low category 2) the factors which consisted of education level and group communication’s behavior included in the lowest category. Number of family, cosmopolitan nature, time allocation, intensity of following the program socialization included in low category. Experience of farming business included in high category 3) the correlation test showed the factors which significantly related to farmers’ participation were education level, cosmopolitan nature, group communication’s behavior, and intensity of following the program socialization. The related factors which were not significant with farmers’participation were number of family, experience of farming business, and time allocation.